Hợp chất lignan glycosid mới từ cây bù dẻ râu Uvaria fauveliana - Đức, Hồ Việt; Hoài, Nguyễn Thị; Thảo, Đỗ Thị; Tài, Bùi Hữu; Minh, Châu Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2014)
Chemical investigation of the aerial parts of Uvaria fauveliana yielded one new lignan glycoside, (8S,8’S)-4,4’-dihydroxy-3,5,3’,5’-tetramethoxy-8,8’-butyrolignan 9-O-α-L-rhamnopyranoside (1), along with two known compounds, oxoanolobine (2) and ergosta-4,6,8(14),22-tetraen-3-one (3). Their chemical structures were established by NMR, HR-MS analysis and in comparison with the reported data. Compounds 2 and 3 displayed moderate cytotoxicity against human lung adenocarcinoma cancer cell line (LU-1) with IC50 values of 9.22±1.02, 10.21±1.16 μg/mL, respectively. Keywords: Uvaria fauveliana, lignan glycoside, cytotoxicity